2007
DOI: 10.1007/s00004-007-0045-y
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Architecture Could Be Good for You

Abstract: Abstract. The deployment of fractal principles in art and architecture seems to be a phenomenon of all times, and is in no way restricted to the period after the systematic mathematical understanding and description of fractals from the1970s onwards. Nowadays, computer-generated fractal art, and the software to generate it, are widely available on the Internet. Fractal principles are also at work in more "traditional" arts or crafts, such as some Dalì paintings, mandalas, mosaics, floor decorations, and so on.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 8 publications
0
15
0
6
Order By: Relevance
“…This natural inclination has been scientifically defended by multiple researchers who propose that the extent to which an urban space is fractal directly impacts the ability for that space to be coherent and livable (Joye, 2007; Salingaros & West, 1999). The work presented here extends this to the complexity within fractal layouts themselves, suggesting that certain levels of D allow for greater comprehensibility in navigation.…”
Section: Discussionmentioning
confidence: 99%
“…This natural inclination has been scientifically defended by multiple researchers who propose that the extent to which an urban space is fractal directly impacts the ability for that space to be coherent and livable (Joye, 2007; Salingaros & West, 1999). The work presented here extends this to the complexity within fractal layouts themselves, suggesting that certain levels of D allow for greater comprehensibility in navigation.…”
Section: Discussionmentioning
confidence: 99%
“…These patterns allow users of the built environment to feel connected to nature, which gives a sense of comfort, contemplation and absorption. This connection also reduces stress due to a shift in focus and enhances concentration (Joye, 2007).…”
Section: Change and Metaphor Of Biomorphic Formsmentioning
confidence: 94%
“…A long list of empirical and experimental studies has revealed the importance of the connection between humanity and nature (Biederman & Vessel, 2006;Joye, 2007;Masden & Salingaros, 2014;Ulrich, 1983Ulrich, , 1984. For example, Ulrich (1983) suggested in his psychoevolutionary theory that exposure to safe, natural areas is inherently restorative, because such settings were associated with survival during humanity's long evolutionary history.…”
Section: Nature and Learning Spaces: Psychological And Experimental Findingsmentioning
confidence: 99%
“…The self-similar fractal 2 complexity of our bodies responds favourably when we perceive similar patterns in the world around us, whether these are the patterns of leaves and flowers or the sounds of moving water and flowing wind (Purcell et al, 2001). As a society, we find less crime in areas where trees and vegetation are abundant (Kuo and Sullivan, 2001), and our bodies’ preference for fractal geometry also shows up cross-culturally in the artwork (Short, 1991) and architecture (Joye, 2007) that we use to create our own aesthetically pleasing environments. A systemic perspective lets us see that it is neither mysticism nor wishful thinking to say we (as embodied beings) are an interlinked part of something larger (a society, ecosystem or global population) but simply a statement of how we came to be who and what we are on whatever level we choose to study.…”
Section: Where Ecosociology Lost Its Waymentioning
confidence: 99%